Terms of Address Showing Disrespect in Orange is the New Black - Sufi Adenda; Ni Gusti Ayu Roselani (Lexicon, 2018)
This research investigates terms of address showing disrespect in a television series entitled Orange Is the New Black. The data used in this research were utterances containing terms of address showing disrespect found in the first eight episodes of season one of the series. 107 terms of disrespect addresses were found, which were then analyzed using Allan and Burridge’s (2006) and Dunkling’s (1990) categories of insults. The results show that the most frequently used category of insults in the series (43%) was the comparison of people with animals category and the Hispanics express the disrespect address terms the most (6.1 disrespect address terms per 1000 words) in comparison with the African-Americans (5.5) and the Caucasians (1.5).